PARP7 inhibition stabilizes STAT1/STAT2 and relieves experimental autoimmune encephalomyelitis in mice - Jiashu Xu; Tao Yu; Zongwei Yue; Xuan Lu; Yandong Zhang; Lei Wang; Samaneh Shabani Åhrling; Michael R. Smith; Yan Chun Li; Jason Matthews; Hening Lin (Cell Reports)
Summary: The regulation of type I interferon signaling is crucial for precisely tuning the innate immune response to combat pathogen invasions, fight cancer, and prevent autoimmune diseases. PARP7, a mono-ADP-ribosyltransferase also called TiPARP (tetrachlorodibenzo-p-dioxin [TCDD]-inducible PARP), is reported to inhibit the production of type I interferons. Here, we find that PARP7 suppresses type I interferon signaling instead of interferon production. PARP7 ADP-ribosylates and promotes the ubiquitination of signal transducer and activator of transcription 1 (STAT1) and STAT2, which recruits p62 to promote the degradation of STAT1 and STAT2 through autophagy. By reducing STAT1 and STAT2 levels, PARP7 decreases type I interferon signaling. We further show that the inhibition of PARP7 promotes type I interferon signaling and relieves experimental autoimmune encephalomyelitis (EAE) symptoms in mice. Our findings revealed a molecular mechanism via which PARP7 suppresses type I interferon signaling, offering insights into the immune-modulatory function of PARP7 and suggesting PARP7 inhibition as a potential treatment strategy for multiple sclerosis.